The Features of Comorbidity of Stroke in The Indonesian Population: Findings from The Indonesian Family Life Survey (IFLS-5) - Muvida; Filzah Amar (Magna Neurologica, 2024)
Background: Comorbidities are associated with a worse stroke prognosis and more challenging clinical management. However, population-based research related to stroke comorbidities in Indonesia is still limited. Objective: This study aims to evaluate the features of important comorbidities among stroke patients in the Indonesian population. Methods: The data was taken from the 2014–2015 Indonesian Family Life Survey (IFLS-5), which represents 83% of the Indonesian population. Data were analyzed by means of logistic regression models using statistical software for data science (STATA) 13. Results: There was a statistically significant relationship between stroke history and several comorbidities risk factors. The risk of stroke increases in individuals with hypertension (odds ratio (OR): 7.97, 95% confidence interval (CI): 5.19-12.26), diabetes (OR: 1.90, 95% CI: 1.14-3.15), heart disease (OR: 2.67, 95% CI: 1.47-4.85), and hyperlipidemia (OR: 3.68, 95% CI: 2.40-5.64). Of the 309 stroke patients, 41.9% had one comorbid condition; 24.1% had two; and 10.5% had three. Comorbidities increase with age, and 80.50% of stroke patients with comorbidities are aged 50 years or more. Conclusion: This study showed that the most common comorbidities in stroke patients in Indonesia are hypertension, hyperlipidemia, and diabetes.